Languages without grammar?: Typological comparison of the morphosyntax of numerals in German sublanguages Sprachen ohne Grammatik? Die Morphosyntax von Numeralia in deutschen Sondersprachen im typologischen Vergleich - Schäfer, Lea; Schallert, Oliver (Sprachwissenschaft, 2019)
Research has so far assumed that German sublanguages (i.e. secret languages, sociolects, and dealer languages) do not have any independent grammatical structures. Taking the morpho-syntactic structure of numerals as an example, this article shows that grammatical patterns of the donor languages that clearly differ from German (Romani, Yiddish, Hebrew) can also become productive in those languages.
CRIS-Team Scopus Importer:2024-10-21